An analysis of critical success factors for product-service systems in an emerging economy - Beuren, Fernanda Hänsch; Ferreira, Marcelo Gitirana Gomes; Moro, Suzana Regina; Cauchick-Miguel, Paulo Augusto (Brazilian Journal of Operations & Production Management, 2023)
Goal: To identify and analyze critical success factors (CSF) related to product-service system (PSS) use and implementation. Design / Methodology / Approach: Firstly, CSF were identified in literature and grouped in three PSS dimensions: (i) offering, (ii), consumer, and (iii) provider. Secondly, a questionnaire was applied to scholars to assess and prioritize those factors through field research. Finally, hypotheses were formulated and statistically verified through Kolmogorov-Smirnov tests. Results: There is an agreement between the expert assessment and the literature on PSS. For instance, life-cycle perspective and PSS cost-benefit needed to be considered since PSS design. However, there are some contingencies about the product dematerialization, as well as to the reduction of environmental impacts. Limitations of the investigation: The CSF were prioritized by the assessment of a limited number of scholars and practitioners from an emerging economy. Practical implications: The CSF of PSS identified and prioritized in this work can offer directions the academics and practitioners, which intend to implement a PSS business model to establish and improve their practices. Originality / Value: PSS is currently considered an alternative to mitigate environmental impacts since one of its purposes is consumption towards dematerialization. Although the concept of PSS has evolved in the past years, the literature is scarce of publications discussing the CSF that could favor its implementation, especially in developing countries.